2023
DOI: 10.2147/ijwh.s406048
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Treatment for Pelvic Organ Prolapse: Vaginal Pessary versus Surgery

Abstract: Background Pelvic organ prolapse (POP) is quite common and has an impact on quality of life (QoL). The evaluation of QoL after treatment for prolapse is important. The objective was to compare patient’s prolapse symptoms, functional outcomes, and quality of life between pessary and surgery using standardized questionnaires at 1 and 6 months after treatment. Methods We conducted a prospective study including women with symptomatic POP who chose pessary or surgery as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
0
1
Order By: Relevance
“…The most common reasons for discontinuation or switching to another treatment method were inadequate symptom relief and a mismatch of expectations in the recommendations group, followed by excessive vaginal discharge, vaginal pain, discomfort, preference for surgery, and pessary expulsion in the pessary group, which are consistent with other studies [6,10,14,19,22,27]. In our study, we did not undertake follow-up visits with the women; this is why we could not encourage them to carry out further pelvic floor muscle training or adhere to lifestyle changes.…”
Section: Secondary Outcomessupporting
confidence: 89%
See 1 more Smart Citation
“…The most common reasons for discontinuation or switching to another treatment method were inadequate symptom relief and a mismatch of expectations in the recommendations group, followed by excessive vaginal discharge, vaginal pain, discomfort, preference for surgery, and pessary expulsion in the pessary group, which are consistent with other studies [6,10,14,19,22,27]. In our study, we did not undertake follow-up visits with the women; this is why we could not encourage them to carry out further pelvic floor muscle training or adhere to lifestyle changes.…”
Section: Secondary Outcomessupporting
confidence: 89%
“…Women in the surgery group had a greater quality-of-life impairment at baseline with respect to general health perception, daily role limitations, the impact on emotions, and the POP severity measures when compared with the other two groups. These findings are in line with another study, where women in the surgery group showed greater impairment in role limitations, physical and social limitations, and emotional problems at the baseline when compared with pessary users [22]. It appears that women who experience more symptoms of POP and a greater impairment in quality of life are more likely to choose and undergo surgery.…”
Section: Secondary Outcomessupporting
confidence: 89%
“…From the corresponding ultrasound indicators, we found that the improvement of ΔBSD in the PFMT + P group was more obvious, which was consistent with the improvement trend of POP in physical examination, and also reflects the consistency of 2 detection methods for evaluating the stage of prolapse (Ba point in POP-Q system and numerical description of BSD in ultrasound examination) ( 16 ). Compared with other reported figures ( 17 - 20 ), prolapse-specific symptoms reduced significantly in the patients of the PFMT + P group, measured by the PFDI-20 at 6 and 12 months, which may be related to the direct improvement of cystocele and restoration of bladder urination function by the uterine support from the perspective of physical support.…”
Section: Discussioncontrasting
confidence: 55%